AN ANALYSIS OF THE PERCEPTIONS OF PARENTS AND EDUCATORS ON DARE COUNTY SCHOOLS’ SPANISH DUAL LANGUAGE IMMERSION PROGRAM - Parker, Keith (East Carolina University, 2019)
Bilingual education is an emerging trend that can be found in many American public schools. Increasingly, schools are looking towards dual language immersion programs to foster increased cultural awareness, stronger literacy skills, and innovative school transformation. The purpose of this study was to understand the perceptions of parents and educators in Dare County Schools on effective dual language immersion programs. The InQuiry process was used in this study to understand the perspective of the participants. This process combines a sorting activity and follow-up focus groups to gather both qualitative and quantitative data. Five distinct perspectives emerged from the data collected in this study: (1) Equity and Innovation, (2) Academic Achievement, (3) Social Awareness and Cognition, (4) Multiculturalism and Academic Achievement, (5) High-Quality Instructional Programs and Teacher Professional Development. The study findings indicate that participants have a high preference for increased cultural awareness and literacy development; two characteristics that are often associated with highly effective dual language immersion programs. The implications of this research suggest the district will be well served to pair the integration of a robust global education curriculum with the dual language immersion program.
Keywords: dual language immersion; Spanish immersion; Q Methodology; global education; Education, Bilingual--North Carolina--Dare County; Immersion method (Language teaching); Elementary school teachers--North Carolina--Dare County--Attitudes